AN EMPIRICAL APPROACH ON LABOUR COSTS FOR OIL FIELD DEVELOPMENT PLANNING - Herlan Adim (Testing Center for Oil and Gas LEMIGAS, 2002)
In planning the development of an oil reservoir, the guidelines should be the annual production targets for a five-year period and for the year when development is scheduled to reach its peak. The production targets must be coordinated with the planned development of the oil industry as a whole. The planned oil production targets for the industry as a whole must be apportioned between different oil-bearing areas and different fields within an area. The development plan for each field should ensure the most efficient production, i.e, at the lowest possible cost. The recommended procedure is first to have a wide grid of wells so as to get a better idea of the reservoir and to finalise the spacing of the planned wells.